CURRENT VIEWS ON URATE NEPHROPATHY IN CHILDREN (World Bulletin of Public Health, 2024)
The problem of urate nephropathy in children in modern literature sources is covered rather rarely and contradictorily. There are many disagreements in the issues of terminology and pathogenesis. Based on the results of long-term scientific research, analysis of modern literature concerning purine metabolism disorders in children, the authors made an attempt to express their point of view on the above-mentioned issues
Keywords: hyperuricemia; urate nephropathy; urolithiasis; urates